A novel phosphocholine‐mimetic inhibits a pro‐inflammatory conformational change in C‐reactive protein. Issue 1 (5th December 2022) - Zeller, Johannes; Cheung Tung Shing, Karen S; Nero, Tracy L; McFadyen, James D; Krippner, Guy; Bogner, Balázs; Kreuzaler, Sheena; Kiefer, Jurij; Horner, Verena K; Braig, David; Danish, Habiba; Baratchi, Sara; et al.
Abstract: C‐reactive protein (CRP) is an early‐stage acute phase protein and highly upregulated in response to inflammatory reactions. We recently identified a novel mechanism that leads to a conformational change from the native, functionally relatively inert, pentameric CRP (pCRP) structure to a pentameric CRP intermediate (pCRP*) and ultimately to the monomeric CRP (mCRP) form, both exhibiting highly pro‐inflammatory effects. This transition in the inflammatory profile of CRP is mediated by binding of pCRP to activated/damaged cell membranes via exposed phosphocholine lipid head groups. We designed a tool compound as a low molecular weight CRP inhibitor using the structure of phosphocholine as a template. X‐ray crystallography revealed specific binding to the phosphocholine binding pockets of pCRP. We provide in vitro and in vivo proof‐of‐concept data demonstrating that the low molecular weight tool compound inhibits CRP‐driven exacerbation of local inflammatory responses, while potentially preserving pathogen‐defense functions of CRP. The inhibition of the conformational change generating pro‐inflammatory CRP isoforms via phosphocholine‐mimicking compounds represents a promising, potentially broadly applicable anti‐inflammatory therapy. Synopsis: A novel low molecular weight compound C10M was designed to block the PC binding site on pCRP, thereby inhibiting the formation of the pro‐inflammatory isoforms pCRP*/mCRP, and thus showing broad anti‐inflammatory effects in vitro and in vivo . The feasibility of the monovalent approach of PC binding site inhibition was demonstrated directly by X‐ray crystallography. The pro‐inflammatory conformational change of pCRP was blocked by a novel monovalent inhibitor utilizing the PC binding site, leaving the B‐face otherwise accessible. The compound C10M inhibited pCRP*/mCRP‐dependent pro‐inflammatory effects on endothelial cells, monocytes and leukocytes in vitro . pCRP*/mCRP‐driven inflammation in renal ischemia/reperfusion‐injury and VCA hindlimb rejection in vivo was markedly inhibited by C10M. Abstract : A novel low molecular weight compound C10M was designed to block the PC binding site on pCRP, thereby inhibiting the formation of the pro‐inflammatory isoforms pCRP*/mCRP, and thus showing broad anti‐inflammatory effects in vitro and in vivo .